Polypyrrole Derivatives in the Design of Electrochemically Driven Actuators - Ward, Meryck; Baker, Priscilla; Iwuoha, Emmanuel; Aubert, Pierre-Henri; Plesse, Cedric (Mini-Reviews in Organic Chemistry, 2015)
Recent developments in the field of biomimetic systems demand mechanical systems that are capable of delivering high power output per volume or mass. Volume changes within the conducting polymer layers are caused by the oxidation or reduction of the polymer. This volume change is the main source for actuators bending or deforming. Different actuator designs have been explored over the years to maximize bending, displacement or deformation. The bilayer design (two layers) incorporates a highly conductive metal layer along with the conducting polymer layer in its design. Trilayer designs (three layers) utilize an electrolyte storage layer to avoid delamination within the design. The storage layer allows for the trilayer design to operate freely in both liquid and air environments. To a limited extent zig zag conformations of polymers linked by small organic molecules or metal coordinating ligands have also been explored in the search for actuator materials with significant deformation and high current density. This review evaluates the contribution of polypyrrole and its derivatives in these actuator designs that impact on maximum displacement capability, current density and the lifetime of these actuator systems.
Keywords: polymer conformations